2013
DOI: 10.1016/j.bbadis.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α-activated mesenchymal stem cells promote endothelial progenitor cell homing and angiogenesis

Abstract: Mesenchymal stem cells (MSCs) accelerate regeneration of ischemic or injured tissues by stimulation of angiogenesis through a paracrine mechanism. Tumor necrosis factor-α (TNF-α)-activated MSCs secrete pro-angiogenic cytokines, including IL-6 and IL-8. In the present study, using an ischemic hindlimb animal model, we explored the role of IL-6 and IL-8 in the paracrine stimulation of angiogenesis and tissue regeneration by TNF-α-activated MSCs. Intramuscular injection of conditioned medium derived from TNF-α-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
96
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 42 publications
4
96
0
1
Order By: Relevance
“…These features, which were significantly different from those of hASCs in 2-dimensional cultures, were likely due to the unique topography cues of DSAF: the DSAF scaffolds had porous nanofibrous structures, which have been reported to affect cellular morphology and function [19, 2123]. Others have reported that seeded hASCs stabilized HUVECs in vitro and that the paracrine activity of hASCs facilitated tissue angiogenesis in vivo [24]. For this reason, we applied co-cultured hASCs and HUVECs to re-endothelialize DSAF in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These features, which were significantly different from those of hASCs in 2-dimensional cultures, were likely due to the unique topography cues of DSAF: the DSAF scaffolds had porous nanofibrous structures, which have been reported to affect cellular morphology and function [19, 2123]. Others have reported that seeded hASCs stabilized HUVECs in vitro and that the paracrine activity of hASCs facilitated tissue angiogenesis in vivo [24]. For this reason, we applied co-cultured hASCs and HUVECs to re-endothelialize DSAF in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These data support the concept of fibroblast subset specialization depending upon their cellular origin. Accumulating evidences also demonstrate that BM-MSC promote angiogenesis through the recruitment of endothelial progenitor cells [17], the differentiation into endothelial cells and pericyte-like cells [18], [19], the secretion of soluble angiogenic factors such as Vascular Endothelial Growth Factor(VEGF)-A or basic Fibroblast Growth Factor (bFGF), and the release of exosomes as well [20][23].…”
Section: Introductionmentioning
confidence: 99%
“…(11) Theoretically, the TNF-α-activated MSCs are able to express various pro-regenerative growth factors, particularly VEGF, platelet-derived growth factor (PDGF), and fibroblast growth factor (FGF), that can activate fibroblasts and impact on collagen synthesis. (9) Previous studies have reported that MSCs activated by the pro-inflammatory cytokine interferon gamma (IFN-γ) are able to increase wound regeneration and tensile strength that is correlated with the amount of collagen. (13) On the other hand, MSCs that are activated in vitro by TNF-α, lipopolysaccharide (LPS) and hypoxia, are able to increase the production of growth factors, particularly VEGF, (14) but the role of TNF-α-activated MSCs on VEGF concentrations and their relationship with collagen are as yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…(1,8) Several potent pro-inflammatory cytokines, particularly TNF-α, play an important role in MSCs activation. (9,10) Activated MSCs release various molecules, such as prostaglandin E 2 (PGE 2 ) that will bind to their EP4 and EP2 receptors on macrophages, so effecting the polarization of macrophages from the inflammatory into the regenerative type. (11) This is marked by the release of the anti-inflammatory interleukin-10 (IL-10).…”
Section: Introductionmentioning
confidence: 99%